(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Taking care of the famous and incredible objects created by humans is what cultural heritage is all about. Different countries have distinct cultures and traditions that are dear to them. It is their country’s identity and a big source of revenue in the tourism industry. The manner of life of a given group of people is referred to as culture. Culture does not remain static since each generation adds to the collective experience of the world and discards what is no longer useful. Anything that is deemed valuable enough to be passed down to future generations is termed heritage. Individual identities are shaped by historic buildings, monuments, and objects. Cultural heritage is particularly susceptible in times of armed conflict, when the destruction of archaeological sites or religious or scientific artefacts may have a negative influence on human identities. Unfortunately, armed war has wreaked havoc on cultural heritage in conflict-affected countries, particularly in recent years. The is study focuses on the topic of preserving tangible and intangible cultural assets during times of armed conflict.